Septipyridines as conformationally controlled substitutes for inaccessible bis(terpyridine)-derived oligopyridines in two-dimensional self-assembly - Caterbow, Daniel; Künzel, Daniela; Mavros, Michael G.; Groß, Axel; Landfester, Katharina; Ziener, Ulrich (Beilstein Journal of Nanotechnology, 2011)
The position of the peripheral nitrogen atoms in bis(terpyridine)-derived oligopyridines (BTPs) has a strong impact on their self-assembly behavior at the liquid/HOPG (highly oriented pyrolytic graphite) interface. The intermolecular hydrogen bonding interactions in these peripheral pyridine units show specific 2D structures for each BTP isomer. From nine possible constitutional isomers only four have been described in the literature. The synthesis and self-assembling behavior of an additional isomer is presented here, but the remaining four members of the series are synthetically inaccessible. The self-assembling properties of three of the missing four BTP isomers can be mimicked by making use of the energetically preferred N–C–C–N transoid conformation between 2,2'-bipyridine subunits in a new class of so-called septipyridines. The structures are investigated by scanning tunneling microscopy (STM) and a combination of force-field and first-principles electronic structure calculations.
Keywords: oligopyridines; self-assembled monolayer; STM